2015
DOI: 10.5811/westjem.2014.11.23592
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Lawsuits Related to Point-of-Care Emergency Ultrasound Applications

Abstract: IntroductionNew medical technology brings the potential of lawsuits related to the usage of that new technology. In recent years the use of point-of-care (POC) ultrasound has increased rapidly in the emergency department (ED). POC ultrasound creates potential legal risk to an emergency physician (EP) either using or not using this tool. The aim of this study was to quantify and characterize reported decisions in lawsuits related to EPs performing POC ultrasound.MethodsWe conducted a retrospective review of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 10 publications
(11 reference statements)
0
35
0
3
Order By: Relevance
“…82 The interesting alternative situation is that lawsuits have been filed for failure to perform point-of-care ultrasonography in cases of diagnostic uncertainty. [83][84][85] A review of all reported US state and federal cases from 2008-2012 found 5 appropriate cases involving emergency physicians and point-of-care ultrasonography. All 5 cases alleged a failure to perform timely ultrasonography within the physician's scope of practice, resulting in morbidity or death.…”
Section: Impact Of Focused Cardiac Ultrasonographymentioning
confidence: 99%
“…82 The interesting alternative situation is that lawsuits have been filed for failure to perform point-of-care ultrasonography in cases of diagnostic uncertainty. [83][84][85] A review of all reported US state and federal cases from 2008-2012 found 5 appropriate cases involving emergency physicians and point-of-care ultrasonography. All 5 cases alleged a failure to perform timely ultrasonography within the physician's scope of practice, resulting in morbidity or death.…”
Section: Impact Of Focused Cardiac Ultrasonographymentioning
confidence: 99%
“…23,24 Interestingly, two studies spanning over 25 years of American legal cases did not report a single case against an emergency physician who failed to interpret or made a misdiagnosis using PoCUS but did report six successful cases against physicians who failed to perform PoCUS when it was within their scope of practice, leading to the delayed diagnoses and patient demise. 25,26 Although it is inevitable that a physician error will eventually occur with the use of ultrasound by inexperienced physicians, it is also clear that the benefits seem to greatly outweigh the purported harm. Physicians are encouraged to use PoCUS with the standards set by CEUS, CAEP, and other local associations to minimize the risk of error.…”
Section: Lack Of Quality Assurancementioning
confidence: 99%
“…To date, all state and federal court litigation cases involving POCUS involved the failure to perform POCUS or failure to perform it in a timely manner. 3 Acknowledged also by the authors of the review, large-scale RCT data are unlikely to be forthcoming. 2 Evidence supports that FAST has a high specificity.…”
Section: Janeve R Desy and Irene W Y Mamentioning
confidence: 99%